Anti-Aging Potential of Plants of the Anak Dalam Tribe, Jambi, Indonesia - Uce Lestari; Muhaimin Muhaimin; Anis Yohana Chaerunisaa; Wawan Sujarwo (Pharmaceuticals, 2023)
The process of skin aging is a physiological phenomenon that can not be avoided. According to global population data, the rate of aging increases by approximately 13% every year. The impact of skin aging has become a significant concern and challenge for developed countries. Consequently, there has been a search for potential new anti-aging agents. This review aims to provide an overview of the current research status of plants of the Anak Dalam Tribe (Indonesian: Suku Anak Dalam [SAD]; referred to as SAD henceforth) in Jambi Province, Indonesia, for the development of potential new anti-aging agents. One such discovery is a product derived from natural ingredients with the ability to prevent premature aging. These new anti-aging plants have been used for centuries by the Anak Dalam tribe, for treating skin diseases and maintaining skin health through traditional remedies. Recent research on herbal formulations used by the SAD community in Indonesia for skin beauty treatments, reported by Research on Medicinal Plants and Herbs or RISTOJA, indicates that 64 plant species are used for skin care. Among these plants, Toona sinensis, Curcuma heyneana, Curcuma zedoaria, Curcuma longa, and Kaempferia rotunda are the most commonly used medicinal plants with anti-aging properties. T. sinensis is a tree, while the others are herbs. T. sinensis shows the highest potential for development as an anti-aging agent, with its extracts, active fractions, and bioactive quercetin isolates known to possess strong anti-aging activities both in vitro and in vivo. Furthermore, C. heyneana, C. longa, C. zedoaria, and K. rotunda also show potential for further research, and three of them have demonstrated good potential for in vivo anti-aging activities. Only K. rotunda demonstrates relatively weaker antioxidant activity compared to T. sinensis, C. heyneana, C. longa, and C. zedoaria. Nevertheless, K. rotunda can still be developed to search for potential opportunities as agents with other activities, while T. sinensis, C. heyneana, C. longa, and C. zedoaria in the findings could be an opportunity to explore the potential of new anti-aging agents. In conclusion, of the five medicinal plants traditionally used by the SAD in Jambi, Indonesia, C. longa has received the most extensive research and shows potential for the development of anti-aging solutions. C. zedoaria, C. heyneana and K. rotunda show good potential for in vivo anti-aging activity. T. sinensis is the least-studied medicinal plant. Nevertheless, it has potential for development, as it is widely used by the SAD community for both traditional medicine and skin care.